2018
DOI: 10.13031/trans.12548
|View full text |Cite
|
Sign up to set email alerts
|

Application of Acoustic Emission and Machine Learning to Detect Codling Moth Infested Apples

Abstract: Abstract. Incidence of codling moth (CM) ( L.) infestation in apples has been a major concern in North America for decades. CM larvae bore deep into the fruit, making it unmarketable. An effective noninvasive method to detect larvae-infested apples is necessary to ensure that apples are CM-free in post-harvest processing. In this study, a novel approach using an acoustic emission (AE) system and subsequent machine learning methods was applied to classify larvae-infested apples from intact apples. ‘GoldRush’ ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…Insect pests usually bore deep into vegetable/fruit where other techniques may not be able to detect the infestation. Acoustic detection of insect activities is based on distinct sounds made by the larvae displacement when they are feeding or biochemical reactions in the pest-infested food that creates low-intensity ultrasonic sounds [17,95]. For example, crawling and feeding of two insects Callosobruchus chinensis and Callosobruchus maculatus in chickpea (Cicer arietinum) and mung bean or green gram (Vigna radiata) were monitored using a condenser-type microphone probe, with a frequency range of 20-16 KHz, placed inside an acoustic-proof bin [96].…”
Section: Acoustic Techniques For Insect Infestation Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insect pests usually bore deep into vegetable/fruit where other techniques may not be able to detect the infestation. Acoustic detection of insect activities is based on distinct sounds made by the larvae displacement when they are feeding or biochemical reactions in the pest-infested food that creates low-intensity ultrasonic sounds [17,95]. For example, crawling and feeding of two insects Callosobruchus chinensis and Callosobruchus maculatus in chickpea (Cicer arietinum) and mung bean or green gram (Vigna radiata) were monitored using a condenser-type microphone probe, with a frequency range of 20-16 KHz, placed inside an acoustic-proof bin [96].…”
Section: Acoustic Techniques For Insect Infestation Detectionmentioning
confidence: 99%
“…However, most of the studies that applied an AE technique are associated with food quality attributes by mechanically destroying the food. In a recent study, Li et al [17] reported that AE detected codling moth activities in infested apples and they obtained a very high classification rate (83%) utilizing 0.5 s of acoustic signal collection. Also, an attempt was made by Ekramirad et al [105] to authenticate the specific source and signature of acoustic emission in codling moth-infested apples through correlating visually observed larvae activities, such as chewing and locomotion, with patterns in the synchronized signals from the contact Lead zirconate titanate (PZT) sensors.…”
Section: Acoustic Techniques For Insect Infestation Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective culling of fruits on packing lines is influenced by both fruit characteristics, that is colour, size of insect injury, the co-occurrence of other visual defects and operational factors, such as the numbers of fruits sorted per worker-second (Knight and Moffitt 1991). Progress in developing automated defect inspection processes based on machine vision and learning is progressing rapidly (Sofu et al 2016;Gupta et al 2018) and the possibility of detecting internal pests in apples in packinghouses has been explored but does not seem practical due to the handling times required (Li et al 2018).…”
Section: Post-harvest Managementmentioning
confidence: 99%
“…Generally, micrometeorological data in a frost night are multidimensional and nonlinear, which increase the difficulty in prediction. In recent years, it has been applied in solving the issues of classification, function approximation and prediction related to precision agriculture, agricultural water management and bio-meteorology [14][15][16][17][18][19]. Its successfully application in precision agriculture makes frost prediction reliable.…”
Section: Introductionmentioning
confidence: 99%